THE IMPACT OF PARENTING ON THE FORMATION OF AGGRESSIVE ATTITUDES IN EARLY CHILDHOOD - S Nadia Mar-atun Azizah; Chandrawaty Chandrawaty (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2022)
This research aims to be able to find out how parenting is applied by parents, as well as how aggressive children act, and the factors that cause children to be aggressive.  Researchers used a qualitative approach and also used observation and interview methods in order to obtain understanding information related to the impact of parenting patterns on the formation of aggressive attitudes of early childhood. The research subjects were parents of children who attended Tk Aisyiyah Rimbo Bujang aged 5-6 years, as well as both parents or guardians of the child, with data collection using direct observation methods and also using interview methods.  The results of interviews that have been conducted from several parents on average parents apply authoritarian parenting patterns and there are also 8 children with aggressive actions that parents do, namely non-verbal aggression such as pinching, and pinching. So that children also imitate the actions that parents do to children. It can be concluded that the actions of this child's aggressive behavior are intentionally and unintentionally seen by the child's behavior, namely suddenly both verbally aggressive and non-verbal aggressive actions.